THE CONTRIBUTION OF FAMILY SUPPORT TO PREGNANT WOMEN'S DAILY NUTRITION AWARENESS - Siti Fatimah, Okta Zenita; Hidayah, Seventina Nurul; Chikmah, Adevia Maulidya (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Family support plays a vital role in promoting the health of pregnant women, particularly in ensuring they meet their daily nutritional needs. This qualitative case study was conducted in Kelurahan Baru, Pasar Rebo District, East Jakarta, and focused on investigating how family support contributes to increasing pregnant women’s awareness of nutritional adequacy. The study involved pregnant women and their closest family members, selected through purposive sampling. Data were collected using in-depth interviews and focus group discussions to gain a greater insight into how family support influences nutritional behavior. The findings show that husbands and mothers-in-law are perceived as the most influential sources of support. Pregnant women reported receiving emotional encouragement, help with food preparation, and collaborative decision-making, all of which increased their nutritional awareness and consistency in maintaining a healthy diet. Additionally, the study identified the family's nutrition knowledge, communication quality, and access to nutritious foods as key factors that shaped the effectiveness of support. In conclusion, the study emphasizes the importance of involving close family members in maternal nutrition efforts. Empowering families through education and encouraging their active involvement in maternal care can be a strategic approach to improving both maternal and fetal health outcomes during pregnancy.